Intercultural Informal Organizations at University - Jacobsson, Mia (My University, 2004)
Intercultural relations are worth of studying, because they are very common in different kinds of organizations. Not only do they exist in international organizations, but they are also common in national organizations and between organizations cooperating. The study investigated interculturalism in an informal organization at university. The overall objective was to understand and explain how an informal organization functions in an intercultural workplace. Answers were sought to two main research questions: 1) What is the nature of an informal organization and how does it affect behavior? 2) What special aspects does interculturalism introduce into an informal organization? Sub-questions helped to answer these research questions: 2a) Are the needs of staff and organization in an intercultural informal organization (IIO) different from those in a monocultural informal organization? 2b) Does an informal organization satisfy these needs by different means in an intercultural compared to a monocultural workplace? 2c) How are the needs of an IIO and a monocultural formal organization compatible? The important elements of an informal organization are communication, social networks, power & decision-making, conflicts, climate, interaction & group dynamic and social satisfaction & motivation, in which intercultural competence, influence of culture and personality on behavior and intercultural synergy set challenges. This concept provides the theoretical basis to study an IIO. The study used a qualitative case study method. The empirical study focused on two departments of the Faculty of Humanities at the University of Vaasa, which formed two cases. The empirical material was collected through recorded interviews with 22 members of the staff. Overall, the results indicated that much of the information goes through informal channels and that social networks exist and power plays an important role. This supports the claims in the theory. Different cultures influenced the way of working. The Finns avoided conflicts whereas foreigners did not. Tolerance and cultural competence characterized the climate. Financial goals of formal organization caused restrictions and uncertainty. There were differences in interaction and group dynamic between the two IIOs, and this is a precondition for creating synergy. When social relationships are coherent, they influence social satisfaction and motivation in a positive manner. Overall, the results indicated that interculturalism produces positive emotions. The case studies support the concept of the IIO, in which the elements of informal organization with critical factors of interculturalism naturally take their place. The needs of staff and organization in an IIO do not differ greatly from those of a monocultural one, although an IIO sets challenges for practical matters and asks for an extra effort to be made. It satisfies these needs by providing cultural richness. It is difficult to make the needs of the IIO compatible with the increasing goals of the formal structure, which characterizes the Finnish modes of actions. Two ultimate conclusions were drawn. Firstly, the Head of Department had a significant influence on group dynamic and social satisfaction. Secondly, there was a contrast between Anglo-American/Western European cultures and Finnish culture.
Keywords: an informal organization; interculturalism; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|